Factors Associated with the Intensity of Labour Pain during the First Stage in UPTD Puskesmas Malaka Soppeng District - Rosmawati,; Syahriani,; Resmawati, (Jurnal Midwifery, 2025)
Introduction Childbirth is a physiological process that involves significant pain, which in some cases can be extremely intense. The pain experienced during labor results from both physiological reflexes and varying psychological responses among mothers. This study aims to examine the factors associated with the intensity of labor pain during the first stage of labor at Puskesmas Malaka, Soppeng Regency. Method This study employs a quantitative analytical design with a cross-sectional approach to investigate the relationship between independent variables (maternal age, parity, and husband's support) and the dependent variable (labor pain intensity during the active phase of the first stage). The study involved a total sample of 33 participants, selected through a total sampling technique, in which the entire population was included in the sample. Result The results of this study indicate that the intensity of labor pain during the acceleration phase was 2.6, during the dilation phase was 3.8, and during the deceleration phase was 4.7. Statistical analysis of the relationship between maternal age and labor pain intensity showed a correlation coefficient of 0.090 and a probability value of 0.619. This indicates no significant relationship between maternal age and the intensity of labor pain in the first stage, which may be attributed to the subjective nature of labor pain influenced by various other factors. Statistical analysis of the relationship between parity and labor pain intensity revealed a correlation coefficient of (-)0.381 and a probability value of 0.028. This indicates a significant relationship between parity and the intensity of labor pain in the first stage. Primigravida mothers experience childbirth for the first time, leading to higher levels of anxiety, which may contribute to increased pain perception. Furthermore, statistical analysis showed a correlation coefficient of 0.368 and a probability value of 0.035, indicating a significant positive relationship between the husband's support and the intensity of labor pain in the first stage. The husband's role is crucial in maintaining the mother's psychological well-being during childbirth, helping her feel more relaxed and thereby reducing the perceived intensity of pain. Conclusion The results of this study indicate that the intensity of labor pain during the acceleration phase was 2.6, during the dilation phase was 3.8, and during the deceleration phase was 4.7. Statistical analysis of the relationship between maternal age and labor pain intensity showed a correlation coefficient. This indicates no significant relationship between maternal age and the intensity of labor pain in the first stage. Statistical analysis of the relationship between parity and labor pain intensity revealed a correlation coefficient. This indicates a significant relationship between parity and the intensity of labor pain in the first stage